2018
DOI: 10.1530/joe-18-0229
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid hormones stimulate L-arginine transport in human endothelial cells

Abstract: Thyroid hormone activity is associated with L-arginine metabolism and nitric oxide (NO) production, which participate in the cardiovascular manifestations of thyroid disorders. L-arginine transporters play an important role in activating L-arginine uptake and NO production. However, the effects of thyroid hormones on L-arginine transporters in endothelial cells have not yet been evaluated. We measured L-arginine uptake, mRNA expression of L-arginine transporters, endothelial nitric oxide synthase (eNOS) mRNA a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 59 publications
0
4
0
2
Order By: Relevance
“…Toral et al. (2018) have shown that thyroid hormones stimulate Na + ‐dependent and Na + ‐independent L‐arginine transporters and increase NO production induced by calcium ionophore. The increased Arg content in the diet could therefore have stimulated greater T4 secretion by the thyroid in the turkeys.…”
Section: Discussionmentioning
confidence: 99%
“…Toral et al. (2018) have shown that thyroid hormones stimulate Na + ‐dependent and Na + ‐independent L‐arginine transporters and increase NO production induced by calcium ionophore. The increased Arg content in the diet could therefore have stimulated greater T4 secretion by the thyroid in the turkeys.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, an in‐vitro study demonstrated the effect of thyroid hormones on the l‐arginine metabolism (Toral et al . 2018). Consequently, in thyroid dysfunctions, not only the GFR but also changes in the protein metabolism could influence serum SDMA concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…Цікавим є факт, що, згідно з даними досліджень in vitro стимуляція поглинання L-аргініну гормонами ЩЗ пов'язана саме із впливом на транспортери L-аргініну. Припускають, що цей ефект опосередковується активацією рецептора інтегрину αvβ3 і подальшими сигнальними шляхами PI3K, MAPK і внутрішньоклітинного Са 2+ [38].…”
Section: роль та досліджені ефектиunclassified
“…Відомо, що L-аргінін як донатор NН-груп є субстратом для NО-синтази -ферменту, що каталізує синтез найважливішого ендогенного вазодилататора NO в ендотеліоцитах. З огляду на те, що надходження L-аргініну може бути лімітуючим фактором, що модулює утворення NO, його застосування в терапевтичних цілях з метою впливу на ендотеліальну дисфункцію при різних ССЗ, включаючи артеріальну гіпертензію, атеросклероз, рестеноз/посткоронарну ангіопластику та реперфузійне ушкодження, є вкрай доцільним [38]. Доведено також, що L-аргінін знижує активацію й адгезію лейкоцитів і тромбоцитів до ендотелію, пригнічує синтез білків адгезії, запобігаючи утворенню й розвитку атеросклеротичних бляшок, пригнічує синтез ендотеліну-1 -потужного вазоконстриктора і стимулятора проліферації й міграції гладких міоцитів судинної стінки.…”
Section: роль та досліджені ефектиunclassified